Analisis Keandalan Business Class Seat Terpasang Di Pesawat A330-200/300 Garuda Indonesia - Aditia Kusuma Wibawa; Freddy Franciscus; Endah Yuniarti (FTK UNSURYA, 2023)
From January 1, 2021 to June 30, 2021, the AIRBUS A330-200/300 aircraft belonging to PT Garuda Indonesia has experienced 36 cases of damage to the business class seat. These cases most often occur due to external factors on the seat. often damaged by crew of flight attendants as well as technicians working. In the study that discussed the factors that caused the failure of the recline mechanism on the B/E Aerospace Minipod Seat and B/E Aerospace MCX Diamond Seat, then aimed at finding a comparison of reliability and cost benefits with the fishbone method. From the results of the study, it was found that the reliability score obtained with the MAREP rate on the B/E Aerospace Minipod seat was 5.798/1000FH and the B/E Aerospace MCX Diamond seat was 5.551/1000FH. As for the maintenance costs, the results obtained on the B/E Aerospace Minipod require a total cost of US 9,587.59 with an average maintenance seat price of US 24.21/seat and B/E Aerospace MCX Diamond is US 5,134.24 with an average treatment seat of US 53.48/seat in beetwen 6 months.